Global voices on atrial fibrillation: South/Southeast Asia - Rungroj, K.; Arintaya, P.; Surenthirakumaran, R.; Antony Sheron, V.; Powsiga, U.; Kumaran, S.; Shribavan, K. (Elsevier, 2024)
Atrial fibrillation (AF) is a leading cause of mortality and morbidity worldwide.1,2 Despite the improvement in the rate of oral anticoagulant (OAC) use for stroke prevention, the residual risk of remain high.3,4 It is recommended that AF patients require a holistic care approach (ie, ABC [Atrial Fibrillation Better Care] pathway) to improve the outcomes.5–7 In this article, we summarize AF management issues in South and Southeast Asia. The first part refers to the scenario from Thailand, from the COOL-AF (COhort of antithrombotic use and Optimal INR Level in patients with nonvalvular atrial fibrillation in Thailand) registry, which is the most extensive exploration of AF in Thailand and, probably, Southeast Asia. Conduct of a clinical trial to improve warfarin management in Thailand is also described. Subsequent parts refer to highlighting rural challenges in AF care in India [and the KERALA-AF (Kerala Atrial Fibrillation) registry, a large comprehensive AF registry in South Asia]—and in Sri Lanka, we focus on mapping patientpathways and community engagement to enhance AF awareness, etc.
Keywords: Atrial fibrillation; South Asia; Southeast Asia; Anticoagulant; ABC pathway